Evaluation of wild solanaceas as patterns of lulo (Solanum quitoense Lam) and their reaction to Fusarium Sp - Arizala Q, Michael; Monsalvo P, Álvaro; Betancourth G, Carlos; Salazar G, Claudia; Lagos B, Tulio (Revista de Ciencias Agrícolas, 2011)
The main limiting disease in Lulo (Solanum quitoense L.) crops is witing caused by Fusarium oxysporum. In Nariño department (Colombia), researchers have reported incidences between 13% and 20%, which have a tendency to increase. Four wild Solanaceaes such as: S. mamosum, S. hirtum, S. marginatum and S. sessiliflorum were used it aimed to look for pathogen resistance, in order to be grafted on lulo (S. quitoense). From each genotype fifty plants were grafted with both types of graft scion and bud, which were chosen grafted with shooting higher than fifty percent. The best materials were grafted scion S. hirtum and S. marginatum with 92% and 96% of surviving respectively. The field phase took place in the La Caldera village where S. hirtum got a good performance regarding to: plant height, number of branches, average of inflorescences and production (p <0.05) compared with the control (S. quitoense) and S. marginatum. Grafting S. hirtum like stock and S. quitoense as a scion is a good option, due to this type of grafts show a good disease tolerance when it were planted in field with 5.55% of yellowing incidence trigger by Fusarium oxysporum.